New Developments in Maritime Security and Their Impact on International Shipping - Pohlit, Claude (Department of Commercial Law, 2014)
Security has been taken very seriously following the September 11 disaster in the USA. This paper examines the legal issues surrounding the prevention of maritime terrorism, especially IMO and American initiatives, and highlights the effects of these measures on the relationship between shipowners and charterers as well as between carrier and cargo.